Pharmacokinetics of diminazene in female Boran (Bos indicus) cattle - Aliu, Y.O.; Mamman, M.; Peregrine, A.S. (Wiley, 1993)
The disposition kinetics and bioavailability of diminazene in five healthy heifers were determined after single intravenous (i.v.) and intramuscular (i.m.) administration of the drug in sequence with a wash‐out period between administrations of 6 weeks. Intact diminazene in plasma, whole blood and urine samples was analysed using high‐performance liquid chromatography. Nonlinear regression analysis of the i.v. and i.m. data indicated that, for either route, the plasma disappearance curves of diminazene were best described by triexponential equations. The i.v. bolus was followed by rapid and biphasic distribution with half‐life values of 0.04 h and 0.58 h, Vd(ss) was 1.91 ± 0.42 1/kg, elimination half‐life was 31.71 h while CI averaged 1.74 ± 0.40 ml/min/kg. Within 30 min of the i.v. dose, the erythrocyte/plasma partition ratio of diminazene was 0.30 ± 0.15. Diminazene was rapidly absorbed following i.m. administration; t½ka was 0.60 h. Cmax, 4.68 ± 1.12 μg/ml, was attained in 10–15 min and systemic availability was 102.42 ± 7.25%. The half‐life of the terminal disappearance phase was 145.48 h. About 8.26% of the i.m. dose was excreted intact in the urine within the first 24 h of treatment. In vitro, diminazene was bound to bovine plasma albumin to the extent of 38.01–91.10%.